Using Nearpod for improving grammar competence in EFL students in virtual education - Rosa M. Contreras J.; Mary T. Cifuentes R; Kerly J. Feijoó R. (Visión Antataura, 2025)
This study examines the effectiveness of Nearpod, an interactive learning tool, in enhancing grammatical competence among EFL (English as a Foreign Language) students in a virtual education context. A sample of 100 university students from the Language Center, at the fourth level of the redesigned program, was selected and divided into two groups: experimental and control. The experimental group utilized Nearpod in synchronous online classes, whereas the control group did not. The independent variable was the use of Nearpod, while the dependent variables were students' grammatical competence and their perceptions of Nearpod. Data collection involved a pretest, a grammatical competence test, a student perception survey, and a posttest of grammatical competence. The pretest results revealed that 42% of students had low grammatical competence. The perception survey indicated that most students found Nearpod easy to use, motivating, and effective in improving their grammatical skills, though some feedback and activity appropriateness could be enhanced. Posttest results showed significant improvement in grammatical competence in the experimental group, with fewer students scoring below 7 points and more achieving medium and high scores. After that, the triangulated results from the pretest, perception surveys, and posttest offer a comprehensive understanding of Nearpod's impact. The study concludes that Nearpod is an effective tool for enhancing grammatical competence in EFL students in virtual education, significantly contributing to better learning outcomes through student engagement and real-time feedback. By focusing on personalized learning and continuous improvement, Nearpod can further enhance EFL education and other learning areas.